Guidelines to support newly qualified professional nurses for effective clinical practice - Warriodene Hansen; Sibusiso M. Zuma (AOSIS, 2024)
Background: Transitioning to a professional role is difficult for newly qualified professional nurses. Given the challenges that these nurses experience during the transition to practice, support is essential for them to become efficient, safe, confident, and competent in their professional roles. Objectives: The purpose of this study was to explore the transition experiences of newly qualified professional nurses to develop a preceptorship model. Method: This study employed a qualitative approach to purposively collect data. Concept analyses were conducted applying the steps suggested by Walker and Avant, and the related concepts were classified utilising the survey list of Dickoff, James and Wiedenbach's practice theory. Results: A preceptorship model for the facilitation of guidance and support in the clinical area for newly qualified professional nurses was developed. The model consists of six components, namely, the clinical environment, the operational manager and preceptor, the newly qualified professional nurse, the preceptorship, the assessment of learning, and the outcome. Conclusion: The study revealed that newly qualified professional nurses face many transition challenges when entering clinical practice. They are thrown far in, experience a reality shock, and are not ready to start performing their professional role. The participants agreed that guidance and support are needed for their independent practice role. Contribution: The preceptorship model for newly qualified professional nurses would be necessary for the transition period within hospitals. This preceptorship model may be implemented by nursing education institutions as part of their curriculum to prepare pre-qualifying students for the professional role.